(untitled) (Global Journal of Science Frontier Research, 2016)
Zooplankton is an integral component of ecosystem and comprises of microscopic animal life that passively float or swim freely. This serves the functional role on the detrital spectrum in water. Chenugonipally Peddacheruvu tank is one of the irrigation tank. It is a small size tank, located between 16.23° N latitude and 77.8° E longitudes in Gadwal Mandal of Mahabubnagar district in Telangana state. Present work has been conducted on zooplankton analysis samples were collected at 30 days of interval between 7 am to 9 am for a period of two years from July 2012 to May 2013 and from July 2013 to May 2014. During the study period total 40 species of zooplanktons were identified belonging to 5 groups, among all 19 species were observed during the 1 st year (2012-2013), while 21 species of zooplanktons were recorded during the 2 nd year (2013-2014) study. At all the four stations during first year study the dominance of the zooplankton species as follows ;Rotifera > Copepoda > Cladocera > Ostracoda > Protozoa. Similarly during second year study the dominance of the zooplankton species as follows; Copepoda > Cladocera > Rotifera > Protozoa > Ostracoda.